Augmented Cues Facilitate Learning Transfer from Virtual to Real Environments - Cooper, Natalia; Milella, Ferdinando; Cant, Iain; Pinto, Carlo; White, Mark; Meyer, Georg (2016 IEEE International Symposium on Mixed and Augmented Reality (ISMAR-Adjunct), 2016)
The aim of this study was to investigate whether augmented cues that have previously been shown to enhance performance and user satisfaction in VR training translate into performance improvements in real environments. Subjects were randomly allocated into 3 groups. Group 1 were trained to perform a real tyre change, group 2 were trained in a conventional VR setting, while group 3 were trained in VR with augmented cues. After training participants were tested on a real tyre change task. Overall time to completion was recorded as objective measure; subjective ratings of presence, perceived workload and discomfort were recorded using questionnaires. The performances of the three groups were compared. Overall, participants who received VR training performed significantly faster on the real task than participants who completed the real tyre change only. The difference between the virtual reality training groups was found to be not significant. However, participants who were trained with augmented cues performed the real tyre change with fewer errors than participants in the minimal cues training group. Systematic differences in subjective ratings that reflected objective performance were also observed.